#### Answer

$B, C, B, C$

#### Work Step by Step

The rule $a^0 = 1$
$6^0 = 1$
$-6^0 = -1$
$(-6)^0 = 1$
$-(-6)^0 = -(1) = -1$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$B, C, B, C$

The rule $a^0 = 1$
$6^0 = 1$
$-6^0 = -1$
$(-6)^0 = 1$
$-(-6)^0 = -(1) = -1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.